Path Analysis of the Relationships between the Eruption Time of the First Primary Teeth and Various Factors in Twins - Birant, Sinem; Veznikli, Mert; Kasimoglu, Yelda; Koruyucu, Mine; Evren, Atif Ahmet; Seymen, Figen (MDPI, 2023)
The timing of primary tooth eruption is critical for children's health planning and the diagnosis of specific growth disorders. The purpose of this study is to assess the relationship between twin pairs' birth weight, gestational age, and gender, which are indicators of prenatal factors; breast-feeding duration, which is an indicator of postnatal factors; type of delivery, which is an indicator of maternal as well as genetic factors; and age of the primary tooth. Twin children aged from 3 to 15 years who applied to the clinic for the first dental examination constituted the sample group. In this twin study, 59 monozygotic (MZ) twin pairs and 143 dizygotic (DZ) twin pairs were included. Genetic (MZ vs. DZ), maternal (type of delivery, gestational age), perinatal (birth weight, gender), and postnatal (duration of breastfeeding) information was obtained, and effects on the children's Eruption Timing of the First Primary Tooth (ETFPT) were examined. Statistical analysis was performed using the consistent partial least squares structural equation model (robust PLSc) technique. As birth weight increased, the age at first eruption became younger, but this change was different between MZ and DZ twins (p < 0.05). While the age at first tooth eruption was older in identical twins who were breastfed for the first 6 months, this increase was not observed in DZ twins. The mean of ETFPT was calculated as 7.31 months in MZ twins and 6.75 months in DZ twins. The effect of breastfeeding and birth weight on ETFPT may differ according to zygosity in twins. MZ twins may tend to take longer to experience the eruption of their first primary teeth.
Keywords: birth weight; breast feeding; child; dizygotic; genetic factors; moderating effect; monozygotic; multi-group analyses; partial least squares; path analysis; structural equation model; tooth eruption age; twins; DECIDUOUS TOOTH EMERGENCE; EARLY-LIFE FACTORS; BIRTH-WEIGHT; LONGITUDINAL ANALYSIS; PRIMARY DENTITION; ENAMEL DEFECTS; CHILDREN; ASSOCIATION; POPULATION; JAPANESE; Pediatrics